2014
DOI: 10.4103/2230-8210.137524
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory T cells, LFA-3 and HLA-DR in autoimmune thyroid diseases

Abstract: Aim:The aim of the present study was to examine the changes in the expression of T-cell activation markers, namely CD4+ CD25+ and CD8+ in patients with AITD, namely Graves’ disease and Hashimoto's thyroiditis as well as colloid nodular goitre. HLA-DR, LFA-3, and peripheral total lymphocytic count are also measured.Materials and Methods:We compared the expression of CD4, CD25, and CD8 surface markers in peripheral blood lymphocyte in Graves’ disease and Hashimoto's thyroiditis as autoimmune thyroid diseases, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…The HLA-DR antigen, which is encoded by the HLA-II gene, most frequently appears on the cytomembrane of macrophages and B lymphocytes and may aid the host immune system to identify and attack tumor cell ( 28 ). Previously, research regarding HLA-DR concentrated on diseases associated with the immune system ( 29 , 30 ) and solid tumors. Diao et al ( 31 ) indicated that overexpression of HLA-DR is associated with decreased OS in patients with glioma, while Sconocchia et al ( 32 ) reported that HLA class II antigen served as a favorable prognostic marker in patients with colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The HLA-DR antigen, which is encoded by the HLA-II gene, most frequently appears on the cytomembrane of macrophages and B lymphocytes and may aid the host immune system to identify and attack tumor cell ( 28 ). Previously, research regarding HLA-DR concentrated on diseases associated with the immune system ( 29 , 30 ) and solid tumors. Diao et al ( 31 ) indicated that overexpression of HLA-DR is associated with decreased OS in patients with glioma, while Sconocchia et al ( 32 ) reported that HLA class II antigen served as a favorable prognostic marker in patients with colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, AITD are characterized by autoantibodies against three main thyroid proteins (thyroid peroxidase (TPO), thyroglobulin (Tg), and the thyroid-stimulating hormone (TSH) receptor (TSH-R)), infiltration of the thyroid gland by immune cells (e.g., lymphocytes, NK cells, monocytes, and macrophages), the formation of germinal centers in the thyroid gland [8] and dysregulated TSH levels [9,10]. However, some studies have failed to observe a significant difference in peripheral blood immune cell composition between AITD patients and healthy individuals [11], while others report significant differences in particular cell types or in immune marker expression [12]. Immune cells, thyroid autoantibodies, and secreted proteins including cytokines may play critical roles in AITD development [13] and in immune responses, including in antibody-dependent cell-mediated cytotoxicity (ADCC) pathways [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have failed to observe a significant difference in peripheral blood immune cell composition between AITD patients and healthy individuals 15 , whereas others have reported significant differences in particular cell types or specific marker expression on immune cells. 16 . Immune cells, thyroid autoantibodies, and secreted proteins including cytokines may play critical roles in AITD development 17 and could participate in immune responses including antibody-dependent cell-mediated cytotoxicity (ADCC) pathways 18, 19 .…”
Section: Introductionmentioning
confidence: 99%